Surgical Techniques for Thoracolumbar Spine Fractures: WFNS Spine Committee Recommendations - Salman Sharif; Yousuf Shaikh; Onur Yaman; Mehmet Zileli (Neurospine, 2021)
To formulate the specific guidelines for the recommendation of thoracolumbar fracture regarding surgical techniques and nonfusion surgery. WFNS (World Federation of Neurosurgical Societies) Spine Committee organized 2 consensus meeting. For nonfusion surgery and thoracolumbar fracture, a systematic literature search in PubMed and Google Scholar database was done from 2010 to 2020. The search was further refined by excluding the articles which were duplicate, not in English or were based on animal or cadaveric subjects. After thorough shortlisting, only 50 articles were selected for full review in this consensus meeting. To generate a consensus, the levels of agreement or disagreement on each item were voted independently in a blind fashion through a Likert-type scale from 1 to 5. The consensus was achieved when the sum for disagreement or agreement was ≥ 66%. Each consensus point was clearly defined with evidence strength, recommendation grade, and consensus level provided. A magnitude of prospective papers were analyzed to formulate consensus on various surgical techniques that can be employed to address different types of thoracolumbar fractures. Surgical treatment of thoracolumbar fractures can be a better option over the nonoperative approach, especially for those who cannot tolerate months in an orthosis or cast, such as those with multiple extremity injuries, skin lesions, obesity, and so forth. It generally allows early mobilization, less hospital stay, reduced pulmonary complications, and better correction of sagittal balance. Current available literature fails to demonstrate any statistically significant benefit of fusion surgery over nonfusion in thoracolumbar fractures.